Publish or perish? Don't perish! - Tickamyer, Ann R.; Sachs, Carolyn (Pennsylvania State University, 2018)
Presented by Ann Tickamyer and Carolyn Sachs (Pennsylvania State University), as part of the Annual Gender Capacity Development Workshop hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 27-28 September 2018.